Precarious Employment and Psychosocial Hazards: A Cross-Sectional Study in Stockholm County - Signild Kvart (MDPI AG, 2021)
Precarious employment (PE) has been linked to adverse health effects, possibly mediated through psychosocial hazards. The aim of this cross-sectional study is to explore if higher levels of PE are associated with psychosocial hazards (experiences of violence, sexual harassment, bullying, discrimination, high demands, and low control) and to explore gender differences in these patterns. The study is based on survey- and register data from a sample of 401 non-standard employees in Stockholm County (2016–2017). The level of PE (low/high) was assessed with the Swedish version of the employment precariousness scale (EPRES-Se) and analysed in relation to psychosocial hazards by means of generalized linear models, with the Poisson family and robust variances. After controlling for potential confounders (gender, age, country of birth, and education), the prevalence of suffering bullying (PR 1.07, 95% CI: 1.01–1.13) and discrimination (PR 1.52, 95% CI: 1.00–2.32) was higher among individuals with a high level of PE. Regarding the demand/control variables, a high level of PE was also associated with low control (PR 1.59, 95% CI: 1.30–1.96) and passive work (the combination of low demands and low control) (PR 1.60, 95% CI: 1.23–2.08). Our findings suggest that workers in PE are more likely to experience psychosocial hazards, and these experiences are more prevalent among women compared to men. Future longitudinal studies should look further into these associations and their implications for health and health inequalities.